FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GEJALA GERD PADA SANTRIWATI DI PONDOK PESANTREN AL-HIDAYAH DEPOK TAHUN 2023 - Azkiya Rahim (2023)
Gastroesophageal Reflux Disease is an abnormal condition that arises when stomach contents (pepsin, acid, and bile acids) rise back from the stomach into the esophagus or esophagus, causing various complaints such as heartburn, dysphagia, nausea, and acid regurgitation. This study aims to determine the factors associated with GERD in female students at Al-Hidayah Depok Islamic Boarding School in 2023. The study design used was a cross-sectional study conducted in March-April 2023 at Al-Hidayah Depok Islamic Boarding School in 2023 with a sample size of 108 respondents. The sampling method used was stratified random sampling and the data was analyzed using the Spearman Rank test. The results of statistical analysis showed that there was a relationship between spicy food consumption (p=0.000), acidic food consumption (p=0.000), fatty food consumption (p=0.000), academic stress level (p=0.000), and sleep quality (p=0.003) with GERD. This study shows that there is a relationship between the tendency to consume spicy foods, acidic foods, fatty foods, academic stress levels, and sleep quality with GERD in female students at Al-Hidayah Depok Islamic Boarding School.